2015
DOI: 10.1093/mnras/stv916
|View full text |Cite
|
Sign up to set email alerts
|

On the potentially dramatic history of the super-Earth ρ 55 Cancri e

Abstract: We demonstrate that tidal evolution of the inner planet ('e') of the system orbiting the star ρ 55 Cancri could have led to passage through two secular resonances with other planets in the system. The consequence of this evolution is excitation of both the planetary eccentricity and inclination relative to the original orbital plane. The large mass ratio between the innermost planet and the others means that these excitations can be of substantial amplitude and can have dramatic consequences for the system org… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 73 publications
0
20
0
Order By: Relevance
“…In the first channel, planets form in the disk, and in some cases, angular momentum exchange between the planets and the protoplanetary disk can produce inward migration (e.g., Lin and Papaloizou 1986;Masset and Papaloizou 2003). In the second channel, planets also formed in the disk, but dynamical interactions between multiple planets or a stellar companion greatly affect the final orbital configuration of the system, through a variety of mechanisms such as planetplanet scattering (e.g., Rasio and Ford 1996a), EKL (see below), or secular chaos (Lithwick and Wu 2012;Hansen and Zink 2015). The role of planet or stellar dynamical interactions is motivated by the presence of substantial eccentricities amongst the more distant Jovian population, and the discovery of high obliquities (misalignments between planetary orbital and host star spin directions, e.g., Albrecht et al 2012b).…”
Section: Planetary Systemsmentioning
confidence: 99%
“…In the first channel, planets form in the disk, and in some cases, angular momentum exchange between the planets and the protoplanetary disk can produce inward migration (e.g., Lin and Papaloizou 1986;Masset and Papaloizou 2003). In the second channel, planets also formed in the disk, but dynamical interactions between multiple planets or a stellar companion greatly affect the final orbital configuration of the system, through a variety of mechanisms such as planetplanet scattering (e.g., Rasio and Ford 1996a), EKL (see below), or secular chaos (Lithwick and Wu 2012;Hansen and Zink 2015). The role of planet or stellar dynamical interactions is motivated by the presence of substantial eccentricities amongst the more distant Jovian population, and the discovery of high obliquities (misalignments between planetary orbital and host star spin directions, e.g., Albrecht et al 2012b).…”
Section: Planetary Systemsmentioning
confidence: 99%
“…One clue about the formation history of 55 Cnc e is the fact that it transits whereas the outer planet (P∼4800 days) is claimed, on the basis of HST astrometry, to be inclined to the line of sight by 30 degrees (McArthur et al 2004). Hansen & Zink (2015) showed that if 55 Cnc e formed slightly beyond its current orbitand migrated inwards through tidal dissipation, it would have crossed a pair of secular resonances in the system, which could have boosted its inclination and/or eccentricity. This would increase the tidal heating and potentially devolatilize the planet or drive it to Roche lobe overflow.…”
mentioning
confidence: 99%
“…Gravitational scattering due to overdensities caused by other planets in the vicinity (e.g. Hansen & Zink 2015).…”
Section: Limitations Of Our Modelmentioning
confidence: 99%